Taxonomy of cat gecko, aeluroscalabotes felinus complex in south east asia - Siti Nor Baizurah, Bt Abd Malik Chang. (Universiti Malaysia Sarawak, UNIMAS, 2012)
This study focused on the genus Aeluroscalabotes, belonging to the family Eublepharidae in South-east Asia. Aeluroscalabotes felinus is known to be the only representative of genus. The objectives of this study are to collect data that contribute to further studies in taxonomy and systematic, while demonstrating morphological differences including colouration patterns between populations of A. felinus in South-east Asia using morphometric techniques. The result of cluster analysis showed differences between the populations in Peninsular Malaysia and Borneo, and even within localities in western Borneo (Sarawak). Discriminant function analysis (DFA) revealed the strongest characters to discriminate the populations are forehead and body dorsum colour, ratio of head width to snout vent length and lamellae on fourth toe.